"Rabbit Rescuers": A School-Based Animal Welfare Education Intervention for Young Children. (2nd January 2022) - Williams, Joanne M.; Cardoso, Mayra Padilla; Zumaglini, Silvia; Finney, Amy L.; ,; Knoll, Monja A.
ABSTRACT: This study evaluated the effectiveness of a Scottish SPCA animal welfare education intervention, "Rabbit Rescuers, " on 5- to 7-year-old children's belief in animal minds, rabbit welfare knowledge, attitudes toward cruelty, and attachment to pets. "Rabbit Rescuers" was a one-week intervention comprising daily 15-min rabbit welfare activities delivered in school by classroom teachers. The activities were designed to be age-appropriate and covered key elements of rabbits' behavior and cognitive abilities, welfare needs (including diet, housing, and natural behaviors), and rabbit care including safe handling and health care (role play as vets). A mixed-method longitudinal design was employed comparing three intervention conditions: mechanical rabbits; soft toy rabbits; and control (education as usual). A sample of 123 children from two age groups (Primary 1 [5- to 6-year-olds] and Primary 2 [6- to 7-year-olds]; 65 boys and 58 girls) in one school participated in the study and were interviewed individually before and after the intervention. Multiple mixed-factor ANOVAs showed that children in the intervention groups improved significantly more than control children in terms of rabbit welfare knowledge, understanding of rabbits as sentient, and attachment to pets. There was also a reduction in attitudes that rabbit cruelty is acceptable among the intervention groups at post-test. The intervention was effective for children regardless of their age. Importantly, the intervention had a stronger impact for children interacting with the interactive mechanical rabbits compared with those who interacted with the soft toy rabbits for all the variables, except for attachment to pets. The findings show that animal welfare education can be effective for young children and that age-appropriate activities support children's knowledge acquisition and attitude change relating to animal welfare. Importantly, the results highlight that mechanical or robotic animals might be highly effective animal welfare education resources.